Ovarian remnant causing hemoperitoneum: a rare presentation ovarian remnant syndrome with review of literature - Analise D Mello; Rupa Padwalkar (Barpeta Obstetrics and Gynaecological Society, 2021)
Ovarian remnant syndrome (ORS) results from the presence of residual ovarian tissue after oophorectomy. The most common preexisting conditions include endometriosis, pelvic inflammatory disease and prior abdominal surgery as in these conditions the removal of ovarian tissue becomes difficult. It should be always considered as a differential diagnosis for chronic pelvic pain. A 50 year old postmenopausal multigravida female was diagnosed with hemoperitoneum. She had undergone hysterectomy with bilateral salpingoophorectomy for endometriosis 5 years ago. Laparotomy performed and a 10X16 cm hematoma along with ovarian tissue was evacuated and sent for histopathology which confirmed presence of ovarian cystadenoma tissue with hemorrhage that is consistent with the diagnosis of ORS.